PENGEMBANGAN BUKU CERITA BERGAMBAR DIGITAL UNTUK PEMBELAJARAN IPA KELAS V SEKOLAH DASAR - Astrida, Nabilla; Putri, Riri Tohari; Taofik, Taofik; Apriliana, Anggi Citra (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
The purpose of this study was to determine the feasibility and stages of developing digital picture storybooks as a medium for learning science for grade V elementary school. This research is a research and development (R&D) with the Hannafin & Peck model which has three stages: 1) needs analysis, 2) design, and 3) development and implementation. The validation test was conducted by three expert lecturers consisting of media experts, material experts, and language experts. The results of the validation assessment conducted by three experts showed an overall average value of 95.3% with very valid criteria. The results of the practicality test through student responses at the one-on-one stage showed an average score of 90.7%, the small group stage showed an average score of 91.3%, and the field test stage showed an average score of 94% with a very practical category. Based on the assessment results, digital illustrated storybook learning media for fifth grade science learning is feasible and practical to implement. The findings of this study are expected to help the world of education, especially educators and educational institutions, and can be a source for further research